Relationship between hand hygiene behavior and Staphylococcus aureus colonization on cell phones of nurses in the intensive care unit - Meri Afridayani (Belitung Raya Foundation, 2021)
Background: Healthcare-Associated Infections (HAIs) are infections that often occur in hospitals with Staphylococcus aureus as the primary cause. Staphylococcus aureus is usually found on nurses' hands and easily transferred by contact. Cell phones can be a convenient medium for transmitting bacteria. Accordingly, hand washing is one of the effective ways to prevent the transmission of Staphylococcus aureus.